Magnetically induced heating by iron oxide nanoparticles dispersed in liquids of different viscosities. Issue 13 (September 2020) - Andrade, Ângela Leão; Cavalcante, Luis Carlos Duarte; Fabris, José Domingos; Pereira, Márcio César; Fernandez-Outon, Luis Eugenio; Pedersoli, Davyston Carvalho; Ardisson, José Domingos; Domingues, Rosana Zacarias; Ferreira, José M.F.
Abstract: The AC magnetically induced heating characteristics of uncoated and silica-coated magnetic iron oxide nanoparticles dispersed in liquids of different viscosities were investigated. The aim was to synthesize and prepare uncoated and silica-coated nanoparticles of maghemite, and evaluate their ability to hyperthermically dissipate heat under an applied AC magnetic field when they are dispersed in liquids of different viscosities. A conceptual approach on the relative contributions of the Néel and the Brownian relaxation mechanisms to the hyperthermic heating of these suspensions is proposed. The microstructure, the physical and chemical properties of the uncoated and silica-coated nanoparticles were assessed by transmission electron microscopy; powder X-ray diffraction; 57 Fe Mössbauer spectroscopy; Fourier transform infrared spectroscopy; zeta potential measurements; and conventional chemical analysis. Results of the Rietveld refinement of the XRD patterns and analysis of the collected Mössbauer data are well consistent with maghemite as being the only iron oxide phase. The mean diameters of the uncoated nanoparticles increased from ~6 to 7 nm, to 35 and 78 nm, for added silica coating amounts varying from 1 to 6-fold, respectively. Zeta potential measurements confirmed the efficiency of the nanoparticles sol-gel coating method. When dispersed in low viscosity media (water, triethanolamine, ethylene glycol), uncoated nanoparticles efficiently release heat via both Néel and Brown relaxation mechanisms under an applied oscillating magnetic field, achieving a temperature raise of approximately 21 °C. The silica layers tend to inhibit the Brownian motion of coated particles, making heat dissipation to be preferentially governed by the Néel relaxation of the magnetization vector. This leads to modest rises in temperature of 9 °C when they are dispersed in water or in the PVC (polyvinyl chloride). SAR tests indicate that the maghemite-silica core-shell systems might be useful for advanced technologies in medical practices based on local hyperthermia, particularly in oncology.